A prototype for tracing missing children : a case of Nairobi County - Ndeto, Martin Ndithi (Strathmore University, 2016)
Tracing missing children has been quite hectic for parents and care givers. A missing child is vulnerable to risks associated with drugs; poor health; involvement in criminal activities for survival, assaults, murder, rape and infection with killer diseases. Currently, there is lack of coordination in departments dealing with issues concerning children and no timeliness for the police department in handling this process. In addition, there is no convergence among the agencies involved in child protection. Several solutions have been proposed among them, the “App for the loved ones”; which has a central database and uses short messaging services (SMS) to send search terms that must have an exact match. Social media has been another approach capable of mobilizing volunteers to spread the information concerning the missing child at a fast rate. However, it lacks credibility since any one can author the information. A “CodeSearch” application was introduced in Canada which uses global positioning system (GPS) to send geo-targeted alerts to its subscribers. However, most people tend to have their GPS turned off unless when in use. It is also limited to employees of the CodeSearch partners. This research aims at introducing an expert system that uses ID3 algorithm to populate its knowledge base and an interactive search using the same algorithm. This allows users to interactively search the database, enter details about their missing loved ones if not yet found and notify them whenever the person is found. The search is based on the person’s phenotypes as they cut across the human race. The research is a form of applied research. The sample size was computed through convenience non-probability sampling. Most of the respondents recommended a proper system hence the reason for creating this prototype. The prototype is developed using V-Process methodology since the clarity of the user requirements was high and the technical expertise needed was readily available. The prototype produced 99% accuracy in tracing the missing children in the sample used.
A Research Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Information Technology
Keywords: Prototype; Missing children; Children; Nairobi County; Drugs; ICT